Budget and public corruption in the municipalities of Caquetá (2013)
Colombia as well as other states have difficulties in countering corruption, this phenomenon is considered one of the most damaging scourges for developing nations, by these acts appropriate the funds, affecting the budget of the municipalities, who as local authorities are implementers by investing those resources, it makes the destination that should not legally have to be made, affecting the population in areas such as health, education, roads, etc.. The Caquetá is a department like the rest of the country has been affected by corruption, it was shown by several cases convicted of those charges have also been processes that failed to identify culprits, but the act itself affect the budget of the municipality despite the government elaborated tools to combat this phenomenon.